Critical Analysis of Economic Development Issues in Muslim Countries - Yudistira Tri Wardana; Fauzan Fauzan; M.F Hidayatullah (IFADAH : Jurnal Ekonomi Dan Bisnis Syariah, 2026)
Economic development in Muslim countries faces various challenges stemming from economic, social, political, and institutional factors, which affect the achievement of sustainable societal welfare. This study aims to critically analyze the issues of economic development in Muslim countries from the perspective of Islamic economics. The method used is library research with a descriptive-qualitative approach through the analysis of various scientific literature, books, and relevant research findings. The results of the study show that low governance quality, high levels of corruption, political instability, wealth distribution inequality, and suboptimal human resource development, including women's participation in education and the workforce, are the main factors hindering economic development. On the other hand, the implementation of Islamic economic principles, Concepts like distributive justice, the prohibition of usury, strengthening hisbah institutions, and optimizing the role of the state in creating fair market mechanisms have the potential to support more inclusive and sustainable development. This study concludes that the success of economic development in Muslim countries requires synergy between governance reforms, institutional strengthening, improving human resource quality, and the consistent implementation of Islamic economic values. These findings are expected to serve as a reference for formulating economic development policies focused on justice, welfare, and sustainability